Evidence that a novel serine kinase catalyses phosphorylation of the insulin receptor in an insulin-dependent and tyrosine kinase-dependent manner. - Smith, D M (1988)
Insulin receptor was co-purified from human placenta together with insulin-stimulated kinase activity that phosphorylates the insulin receptor on serine residues. By using this 'in vitro' system, the mechanism of activation of the serine kinase by insulin was explored. Peptide 1150, histone, poly(Glu-Tyr), eliminating Mn2+ (Mg2+ only), treatment at 37 degrees C (1 h), N-ethylmaleimide, phosphate, beta-glycerol phosphate and anti-phosphotyrosine antibody all inhibited insulin-receptor tyrosine kinase activity and the ability of insulin to stimulate phosphorylation of the insulin receptor on serine. Additionally, direct stimulation of the receptor tyrosine kinase by vanadate increased serine phosphorylation of the insulin receptor. Insulin-stimulated tyrosine phosphorylation preceded insulin-stimulated serine phosphorylation of the insulin receptor. The activity of the insulin-sensitive receptor serine kinase was not augmented by cyclic AMP, cyclic GMP, Ca2+, Ca2+ + calmodulin, Ca2+ + phosphatidylserine + diolein or spermine, or inhibited appreciably by heparin. Additionally, the serine kinase phosphorylated casein or phosvitin poorly and was active with Mn2+. This indicates that it is distinct from Ca2+, Ca2+/phospholipid, Ca2+/calmodulin, cyclic AMP- and cyclic GMP-dependent protein kinases, casein kinases I and II and insulin-activated ribosomal S6 kinase. Taken together, these data indicate that a novel species of serine kinase catalyses the insulin-dependent phosphorylation of the insulin receptor and that activation of this receptor serine kinase by insulin requires an active insulin-receptor tyrosine kinase.